Optimization of Reactive Power Configuration for Offshore Wind Farms - Yuan YANG; Xi YANG; Jiangping TAN; Liang CHEN; Yanli XIN; Xia CHEN (Zhongguo dianli)
According to the reactive power configuration principles of offshore wind farms, this paper analyzes the reactive power losses of offshore wind farms, mainly consisting of wind turbines, submarine cables and main transformers. Under the condition of meeting the requirements of reactive power compensation and power-frequency overvoltage, the capacity of the shunt reactor should be increased as much as possible to obtain the optimal configuration scheme of the shunt reactor and the dynamic reactive power compensation device SVG. Research results show that when the length of the 220 kV submarine cable increases and the wind turbine output decreases, the capacitive reactive power of the offshore wind farm will increase; When the length of the 220 kV submarine cable increases, the no-load overvoltage, the load rejection overvoltage, the single-phase ground fault overvoltage of the offshore wind farm will increase. Finally, based on a real case, the optimal capacity of the shunt reactor and the SVG were obtained. The proposed method is simple, practical and economically feasible, and can be applied in the practical engineering.